Simple Reaction-Diffusion Modeling Predicts Inconspicuous Neighborhood-Dependent Color Subclustering of Lizard Scales - Szabolcs Zakany; Michel C. Milinkovitch (Physical Review X, 2023)
Turing proposed a reaction-diffusion (RD) process as the chemical basis of morphogenesis. Despite the elegance of this model, its relevance for the precise description of morphogenesis in real organisms is largely disputed. Here, we show that a simple RD system, predicting the cellular-automaton-like patterning of ocellated lizards’ skin into green and black labyrinthine chains of scales, additionally predicts unsuspected subtle color subclustering that correlates with the colors of the scales’ neighbors. Hyperspectral imaging indicates that color subclustering is present in real lizards, confirming the numerical model nontrivial prediction. In addition, extensive histological analyses show that melanophores’ spatial distribution correlates with scale neighborhood, confirming that color subclustering is associated to the underlying microscopic system of chromatophore interactions. We then show that the observed subclustering is efficiently captured by RD models, irrespective of their form, discretization, and spatial dimensionality. We also show that sets of values can be identified in the 12-dimensional RD parameter space to yield the correct direction of correlation (i.e., observed in real lizards) between green-scale blackness and their neighborhood configuration, hence instructing the mathematical model. More generally, our results show that subtle mesoscopic properties of biological dynamical systems, as well as some of the underlying microscopic features, are quantitatively captured by simple RD models without integrating the unmanageable profusion of variables at lower scales.